PENGARUH INFRASTRUKTUR DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP PERTUMBUHAN EKONOMI KABUPATEN LANGKAT 2010-2019 - DWI RAYANA SIREGAR; AHMAD ALBAR TANJUNG (Ekonomi & Bisnis, 2020)
Langkat Regency is one of the regencies in North Sumatra Province. Langkat Regency consists of 23 Districts, 37 Sub-Districts and 240 Villages with an area of 6,262.00 km² and has a population of approximately 1,028,309 people. With the large number of residents in Langkat district, it can increase demand for goods and services that can increase economic growth. In the 2010-2019 period, Langkat economic growth continued to increase. This study aims to determine the effect of Road Infrastructure and Human Development Index on Economic Growth in Langkat Regency, especially in the 2010-2019 period. This type of research is literature research with descriptive methods with secondary data. The results showed that a good road infrastructure variable (X1) had no significant effect on Economic Growth in Langkat Regency (Y). Meanwhile, the Variable Human Development Index (X2) has a significant effect on Economic Growth in Langkat Regency (Y).